Exploring the Usability and Engagement of Students in an Educational Board Game on Personal Financial Planning - Osman, Idris; Md Taib, Norraeffa; Abu Yazid, Zarinah; Daud, Shahreena; Othman, Mohd Zailani (Information Management and Business Review, 2024)
Traditional teaching approaches lack engagement, personalization, flexibility, and effective evaluation, thereby limiting learning outcomes. Consequently, these systems face challenges in engaging students, meeting their individual needs, adapting to diverse learning situations, and accurately assessing their competency. Educational board games (EBGs) offer a dynamic and engaging learning experience through play and personalized learning, promising optimal outcomes to overcome these obstacles. The objective of this study is to investigate how usability influences student engagement using the MEEGA+ evaluation approach during EBG play in a Personal Financial Planning course at Universiti Teknologi MARA (UiTM) Cawangan Melaka, Kampus Bandaraya Melaka. This quantitative study involved a self-administered questionnaire and a purposive sample of 200 bachelor’s degree students in the course. PLS-SEM was utilized to assess the model and hypothesized relationships. The operability and accessibility of educational games significantly enhanced student engagement, underscoring the utility of board games for learning through play. Usability, experience, and engagement should be integral considerations in instructional game design. The MEEGA+ assessment model can be applied to evaluate game-based learning across various EBGs. Board games have the potential to enhance educational outcomes, underscoring the necessity for further research in game-based learning. The study also suggests that the MEEGA assessment model can assist designers and educators in developing effective game-based learning experiences.